2018
DOI: 10.5812/ircmj.62735
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cognitive Behavioral Therapy on Depression and Obesity in Women with Polycystic Ovarian Syndrome: A Randomized Controlled Clinical Trial

Abstract: Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder that can cause mental and psychological manifestations such as depression in addition to medical aspects like obesity. Objectives: The aim of this study was to evaluate the effect of cognitive-behavioral therapy on body mass index (BMI) and depression in women with PCOS. Methods: This randomized controlled trial was conducted on 74 women in Saqez-Iran, 2017. Participants were assigned into 2 groups of intervention and control through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…found a reduction in anxiety sensitivity following group cognitive behavioral therapy for social anxiety disorder and panic disorder. Also,Abdollahi et al (2018) and Wesner et al (2019) have shown consistent results with current study in improving quality of life after CBT. The findings ofSadeghi et al (2017) suggested that group cognitive behavioral therapy is effective on enhancing quality of life and resilience in women with breast cancer.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…found a reduction in anxiety sensitivity following group cognitive behavioral therapy for social anxiety disorder and panic disorder. Also,Abdollahi et al (2018) and Wesner et al (2019) have shown consistent results with current study in improving quality of life after CBT. The findings ofSadeghi et al (2017) suggested that group cognitive behavioral therapy is effective on enhancing quality of life and resilience in women with breast cancer.…”
supporting
confidence: 91%
“…One of the most well-known effective interventions used to improve pregnant women's mental health is cognitive behavioral therapy (CBT; Choate et al, 2011), with a stress on importance of the effects of individuals' thoughts on their emotions (Murphy et al, 2017) and behaviors and an effort to modify their emotions through altering thoughts and perception (Mustaffa et al, 2012). Previous studies have shown the effectiveness of CBT on reduction of pregnancy anxiety (Hassan et al, 2020;Hossein Khanzadeh et al, 2017;Loughnan et al, 2018;Surkan et al, 2020;Yazdanimehr et al, 2016), anxiety sensitivity (Boswell et al, 2013;Nowakowski et al, 2016), improvement of quality of life (Abdollahi et al, 2018, Wesner et al, 2019 and resilience (Sadeghi & et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth questioning whether a 16‐week intervention is comparable with a 1‐year intervention, especially in regard to whether the results of a shorter program will be sustained in the future. Other CBT‐based LS for women with PCOS have resulted in a weight loss of 4.3% (16), 2.1% (18), and around 1% (17), respectively, and have not been able to succeed in a 5% to 10% weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Some LS focused on CBT only or included CBT techniques, like the pilot intervention of Cooney and colleagues ( n = 33) that compared 16 individual 30‐minute nutrition/exercise counseling sessions to 8 additional 30‐minute brief CBT sessions (16). Abdollahi and colleagues invested eight CBT sessions of 45 to 60 minutes ( n = 74) compared with a control group whose members received no treatment (17). Oberg and colleagues performed an intervention of 4 months ( n = 68) that included three group meetings per month (18) delivered by a lifestyle coach.…”
Section: Introductionmentioning
confidence: 99%
“…No significant biometric or metabolic changes were noted at either the week 8 or week 16 assessments. Abdollahi et al (2018) also used CBT to improve depression among women with PCOS, reporting only slight improvement. Besides CBT, yoga, aerobic training and exercise have also been tested for the care of women with PCOS.…”
Section: Introductionmentioning
confidence: 99%